Experimental results and computational insight into sequential reactions of β-(2-aminophenyl)-α, β-ynones with aryl isocyanates/benzoyl isothiocyanate. Issue 16 (14th April 2020) - Arcadi, Antonio; Aschi, Massimiliano; Chiarini, Marco; Marinelli, Fabio; Marsicano, Vincenzo; Portalone, Gustavo
Abstract : The selective formation of quinazoline vs. benzoxazine and benzothiazine derivatives from β-(2-aminophenyl)-α, β-ynones and aryl isocyanates/benzoyl isothiocyanate was explored. DFT calculations provide a plausible rationale. Abstract : The investigation on tandem addition/cyclization reactions of β-(2-aminophenyl)-α, β-ynones with aryl isocyanates/benzoyl isothiocyanate is reported. Experimental results show the suitable conditions to selectively direct the reaction outcome towards the product of 6- exo-dig N -, O -, or S -annulation of the in situ generated alkynyl urea/thiourea intermediate. The reaction of a variety of β-(2-aminophenyl)-α, β-ynones with aryl isocyanates/benzoyl isothiocyanate led to the selective formation of quinazoline or benzoxazine/benzothiazine derivatives, respectively. Density functional theory calculations provide a plausible rationale for the reaction outcome.